Psychomotor performance of elite volleyball players during a game - Mroczek, D.; Kawczynski, A.; Superlak, E.; Chmura, J. (Perceptual and Motor Skills, 2013)
Prior studies have found that reaction time and movement time increase with fatigue (measured by blood lactate concentration) in laboratory situations. The study tested whether these relationships occurred for reaction time and movement time of elite volleyball players during a training game. Components of the players' psychomotor performance (reaction time, movement time) and physiological parameters (heart rate, blood lactate concentration) were analyzed. Fourteen male, adolescent volleyball players participated in the study. Reaction time and movement time were measured with the Optojump measurement system during the game in off-the-court periods. All measurements were performed during a pre-game test and during each of the four sets of the game. During Set 1, players' reaction time decreased significantly compared with the pre-game test indicating a likely warm-up effect. Blood lactate concentration increased significantly across sets. However, the players' reaction times remained constant across sets. The studied players did not exceed the psychomotor fatigue threshold anytime during the entire game. These findings indicate that the amount of training (20 hours a week) done by elite players is sufficient to prevent threshold fatigue levels that create significant decreases in psychomotor performance.